Parents Day Program at Islamic Elementary School - Azzahra, Fatimah; Rasmuin, Rasmuin; Firmansyah, Rizky (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to understand the implementation of the Parents Day program in strengthening emotional closeness between parents and children, explore parents' perceptions of the program as an effort to enhance relationships with children and identify the supporting and inhibiting factors of Parents Day activities. Using a phenomenological qualitative approach, the results of this study show that Parents' Day strengthens the emotional closeness between parents and children through interactive activities such as decorating cakes, flowers, hats, and other activities. Its success is evident in its motivation to learn, positive communication between parents, children, and teachers, and positive feedback regarding the benefits of this activity. Thus, overall, Parents Day is proven to significantly contribute to the emotional relationship between parents and children, as well as being an effective means of strengthening family communication and interaction in the school environment, creating a more harmonious atmosphere, and supporting child development.